Google Trends data analysis of hepatitis B and their correlation with hepatitis B early detection program for pregnant women in Indonesia - Nugraha, Dwi Adhi; Pramana, Triyanta Yuli (BKM Public Health and Community Medicine, 2022)
Purpose: Hepatitis B is still a problem in Indonesia. National surveillance project [Basic health survey (Riskesdas)] data in 2013 showed the prevalence of hepatitis B surface antigen (HBsAg) was 7.1%. One effort has been made to reduce the transmission of hepatitis B: the hepatitis B early detection program (DDHB) for pregnant women. Early changes in population health may be reflected in shifts in information and communication patterns on the internet. Changes in information and communication patterns on the internet can be an early "symptom" of changes in population health. This study aimed to know the correlation of hepatitis B relative search volume with HBsAg reactive percentage and coverage of the DDHB program for pregnant women in Indonesia. Methods: The value of relative search volume for hepatitis B in various regions in Indonesia in 2020 based on Google trends correlated with reactive HBsAg percentage and coverage of the DDHB program for pregnant women in 2020. Researchers compared the value of relative search volume for hepatitis B with hepatitis, hepatitis A, and hepatitis C. Spearman correlation analysis test was used to find the relationship between variables. Results: East Nusa Tenggara had the highest hepatitis B relative search volume and reactive HBsAg percentage in the DDHB program for pregnant women in 2020. Hepatitis B relative search volume was correlated with reactive HBsAg percentage (r=0.618; p<0.001) but did not correlate with DDHB coverage (r=-0.65; p=0.374). The popularity of hepatitis B (19.81±6.68) was higher than hepatitis A (8.65±5.79) and hepatitis C (3.90±1.75) but lower than hepatitis alone (54.08±19.02). Conclusion: East Nusa Tenggara had the highest hepatitis B relative search volume and reactive HBsAg percentage. Hepatitis B’s relative search volume in Google Trends data analysis significantly correlated with reactive HBsAg percentage in the DDHB program for pregnant women in Indonesia.